Esboço de uma rede de cooperação em um arranjo produtivo local na indústria calçadista paulista - Queiroz, Timóteo Ramos (Universidade Federal de São Carlos, 2012)
Clusters of companies have been widely studied by gains from the actors that compose them. However, the strong bias for such studies still fall on the economic benefits and very little to address the attributes of social relationships that constitute, integrate and maintain such networks. So, we decided to studies and surveys of clusters, choosing to focus on Local Productive Arrangements (APLs), among the many possible configurations. In order to advance this work in this area has focused on design, characterize and analyze the networks of cooperation between industrial companies in a Local Productive Arrangement (APL) are the footwear of Sao Paulo. It then took the footwear cluster at Jaú, State of São Paulo. The method used for data collection was a questionnaire on the spot for the key players that made up the network and then sending structured questionnaires to companies. The data generated were converted into ordinal qualitative variables, so that it is possible to use the software UCINET version 6.283, to design and measurement network. The analysis provided an understanding and measurement of the relationship networks of enterprises and the network present in APL. It turned out that the social motives for cooperative action by the companies were classified as the same weight as economic reasons.
Sketch of a cooperative network in a local productive arrangement at São Paulo State s footwear industry
Keywords: Engenharia de produção; Redes de relações sociais; Arranjos produtivos locais; Dinâmica de redes; UCINET (Programa de computador); Calçados; Cooperation Networks; Arranjos Produtivos Locais; UCINET; Calçados; ENGENHARIAS::ENGENHARIA DE PRODUCAO